A REVIEW ON CARBON/GRAPHENE QUANTUM DOTS AND THEIR APPLICTAIONS IN ANODE OF LITHIUM-ION BATTERIES - Diwan, Iti; Khare, Purnima Swarup (International Journal of Engineering Technologies and Management Research, 2022)
This article is all about a revolutionary carbon nanomaterial Carbon/Graphene quantum dot “(C/GQDs)". It is known as the world's strongest, lightest, thinnest, and hardest material, with essentially endless sources due to its composition of carbon, which is the fourth most abundant element in the universe. CQDs are carbon nanoparticles that are smaller than 10 nm. Strong and controllable fluorescence emission, structural and chemical stability, wide surface area, electrical conductivity, and low toxicity are just a few of the characteristics of these 0- dimensional QDs. This can be used in a variety of ways. In this paper, we'll discuss about their application in Lithium-ion batteries. These batteries are particularly promising energy storage devices because of their high capacity, fast charge-discharge rates, light weight, and great stability. These rechargeable batteries have proven to be a rising star, with plenty of opportunity to grow in order to meet future energy demands. This study will provide an overview of carbon quantum dots as an anode for Li-ion batteries, as well as the advantages of carbonic anodes. It also explains why carbon quantum dots and their composites are the best anode materials for lithium-ion batteries. We intend to offer a brief overview of several carbon anodes, as well as a thorough examination of various anodic materials that are now accessible.